7
x+1/x=3 => (x+1/x)^2 = 9
but (x+1/x)^2 = x^2 + 1/x^2 + 2 = 9
hence x^2 + 1/x^2 = 7
EDIT: i see that me and sweet and simple understood your question differently.
If you mean (x+1)/x = 3, see her solution
If you mean x + (1/x) = 3, see my solution.
EDIT: thank you sweet and simple
2007-07-05 07:59:03
·
answer #1
·
answered by swd 6
·
3⤊
1⤋
3
2007-07-05 15:03:29
·
answer #2
·
answered by blue 2 1
·
0⤊
1⤋
(x+1)/x = x/x + 1/x = 1 + 1/x
(x^2 + 1)/x^2 = x^2/x^2 + 1/x^2 = 1 + 1/x^2 = 1 + 1/x*1/x
Since 1+ 1/x = 3, that means that 1/x = 2
So
1 + 1/x*1/x = 1 + 2*2 = 5
2007-07-05 14:59:42
·
answer #3
·
answered by jenh42002 7
·
0⤊
1⤋
Depends on exactly what you mean.
Without parentheses, your problem means:
x + (1/x) = 3
But others are assuming you mean:
(x+1)/x = 3
In the former case,
x + (1/x) = 3
x^2 + 1 = 3x
x^2 - 3x + 1 = 0
x = (3 +/- sqrt(5)) /2
In the latter case:
(x+1)/x = 3
x + 1 = 3x
x = 1/2
Assuming the latter,
(x^2 + 1)/(x^2) =
(1/4 + 1)/1/4 =
(5/4) / (1/4) =
5
2007-07-05 14:59:50
·
answer #4
·
answered by McFate 7
·
0⤊
1⤋
x+1/x=3
(x+1/x)^2 = 3^2
x^2 + 2 + (1/x)^2 = 9
x^2 + 1/x^2 = 7
2007-07-05 15:06:07
·
answer #5
·
answered by oregfiu 7
·
1⤊
0⤋
x+1/x=3
x+1 =3x
2x=1
x =1/2
so x^2+1/x^2
= [(1/2)^2 +1] / (1/2)^2
=[1/4 +1] /1/4
=5/4 *4
=5
Edit: Hey starwhitedwarf....u r so sweeet!!!
2007-07-05 14:58:20
·
answer #6
·
answered by sweet n simple 5
·
2⤊
3⤋